Improving irrigated cropping systems on the high plains using crop simulation models - Pachta, Christopher James (Kansas State University, 2007)
Irrigated cropping systems on the High Plains are dominated by water intensive continuous corn (Zea mays L.) production, which along with other factors has caused a decline in the Ogallala aquifer. Potentially demand for water from the aquifer could be decreased by including drought tolerant crops, like grain sorghum (Sorghum bicolor L.) and cotton (Gossypium hirsutum L.), in the cropping systems. This study calibrated the CERES-Maize, CERES-Sorghum, and CROPGRO-Cotton models for the High Plains and studied the simulated effects of different irrigation amounts and initial soil water contents on corn, cotton, and grain sorghum. Input files for calibration were created from irrigated and dryland research plots across Kansas. Information was collected on: soil physical properties, dry matter, leaf area, initial and final soil water content, management, and weather. CERES-Maize simulated grain yield, kernel number, ear number, and seed weight across the locations with root mean square errors (RMSE) of 2891 kg ha-1, 1283 kernels m-2, 1.6 ears m-2, and 38.02 mg kernel-1, respectively. CERES-Sorghum simulated grain yield, kernel number, head number, and seed weight with RMSEs of 2150 kg ha-1, 5755 kernels m-2, 0.13 heads m-2, and 4.51 mg kernel-1. CROPGRO-Cotton simulated lint yield and boll number with RMSEs of 487 kg ha-1 and 25.97 bolls m-2. Simulations were also conducted with CERES-Maize, CERES-Sorghum, and CROPGRO-Cotton to evaluate the effects of irrigation amounts and initial soil water content on yield, evapotranspiration (ET), water use efficiency (WUE), available soil water at maturity, and gross income per hectare. Simulations used weather data from Garden City, KS from 1961 to 1999. Irrigation amounts were different for all variables for corn and grain sorghum. For cotton, yield, WUE, soil water, and gross income were not different between the top two irrigation amounts. For corn and grain sorghum, initial soil water content was only different at 50% plant available water. Initial soil water had no affect on cotton, except for ET at 50%. Simulations showed that cotton yields are similar at lower irrigation. Also, cropping systems that include cotton have the potential to reduce overall irrigation demand on the Ogallala aquifer, potentially prolonging the life of the aquifer.
Keywords: Crop simulation models; Ogallala aquifer; CERES Maize; CERES Sorghum; CROPGRO Cotton; Improving irrigated cropping systems; Agriculture, Agronomy (0285)